Cobalt‐Catalyzed Radical Hydroamination of Alkenes with N‐Fluorobenzenesulfonimides. (28th October 2021) - Qin, Tao; Lv, Guowei; Meng, Qi; Zhang, Ge; Xiong, Tao; Zhang, Qian
Abstract: An efficient and general radical hydroamination of alkenes using Co(salen) as catalyst, N ‐fluorobenzenesulfonimide (NFSI) and its analogues as both nitrogen source and oxidant was successfully disclosed. A variety of alkenes, including aliphatic alkenes, styrenes, α, β‐unsaturated esters, amides, acids, as well as enones, were all compatible to provide desired amination products. Mechanistic experiments suggest that the reaction underwent a metal‐hydride‐mediated hydrogen atom transfer (HAT) with alkene, followed by a pivotal catalyst controlled SN 2‐like pathway between in situ generated organocobalt(IV) species and nitrogen‐based nucleophiles. Moreover, by virtue of modified chiral cobalt(II)‐salen catalyst, an unprecedented asymmetric version was also achieved with good to excellent level of enantiocontrol. This novel asymmetric radical C−N bond construction opens a new door for the challenging asymmetric radical hydrofunctionalization. Abstract : A highly general and efficient Co‐catalyzed radical hydroamination of alkenes with N ‐fluorobenzenesulfonimide and its analogues has been developed. The corresponding asymmetric version has also been achieved by using a chiral cobalt(II)‐salen catalyst in good to excellent level of enantiocontrol.